The efficacy and safety of simple-needling for the treatment of primary dysmenorrhea compared with ibuprofen: A systematic review and meta-analysis. Issue 7 (18th February 2022) - Xuan, Yichen; Zhang, Haifeng; Liu, Duanyong; Huang, Yiyong; Li, Linhui; Cao, Qianan; Fu, Yong
Abstract: Background: Needling and ibuprofen are often used clinically to treat primary dysmenorrhea (PD). However, the difference between the efficacy and safety of the treatment of PD is not clear. This study evaluates the efficacy and safety of simple-needling for PD patients through a comparison with ibuprofen. Methods: A comprehensive search of 7 electronic databases and relevant medical journals, from the establishment of the publication to December 2020. The Cochrane risk of bias tool was used to evaluate the methodological quality of randomized clinical trials (RCTs) that met the inclusion criteria, and a meta-analysis was performed with the Review Manager version (RevMan version 5.3). Results: Twenty three RCTs were included. The meta-analysis reported that simple-needling groups had better than ibuprofen groups on cure rate (relative risk = 2.29, 95% CI [1.96, 2.68], P < .00001) and total effective rate (relative risk = 1.24, 95% CI [1.19, 1.29], P < .00001) and VAS score (MD = −1.24, 95% CI [−1.92, −0.55], P = .0004). Seven studies reported adverse events, of which 4 studies had mild adverse events. Conclusion: Simple-needling is superior to ibuprofen treatment in terms of clinical efficacy and improvement of pain symptoms. A small number of studies reported whether simple-needling produced adverse events, so there is not enough evidence to support the safety of simple-needling in the treatment of PD. PROSPERO registration number: CRD42021233403